2015
DOI: 10.1007/s10854-015-3317-4
|View full text |Cite
|
Sign up to set email alerts
|

Improved piezoelectric and bright up-conversion photoluminescent properties in Ho-doped Bi0.5Na0.5TiO3–BaTiO3 lead-free ceramics

Abstract: Lead-free ceramics of 0.94(Bi 1-x Ho x Na) 0.5 TiO 3 -0.06BaTiO 3 have been prepared by a conventional solid reaction method and their piezoelectric, ferroelectric and photoluminescent properties have been studied. After the partial substitution of Ho 3? for Bi 3? , a new Bi 0.5 Na 0.5 TiO 3 -based solid solution with a pure perovskite structure is formed. The doping of Ho 3? has no obvious influence on the crystal structure of the ceramics. After the addition of a small amount of Ho 3? (x = 0.015), the piezoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…b, the rhombohedral symmetry is characterized by the splitting of (003)/(021) peaks at ∼40° in the 0.94(Bi 0.984 Er 0.016 Na) 0.5 TiO 3 –0.06BaTiO 3 ceramics sintered at 1080–1240 °C for 2 h; and the splitting of (002)/(200) peaks between 46° and 48° are simultaneously observed, corresponding to a tetragonal symmetry. To our knowledge, the simultaneous existence of (003)/(021) peaks at ∼40° and (002)/(200) peaks at ∼46.5° has been frequently considered as a main characteristic of the formation of rhombohedral and tetragonal MPB in BNT‐based materials . However, some researchers reported that the splitting of peaks can be suspected resulting from Kα1 (1.54056 Å) and Kα2 (1.54439 Å) radiations .…”
Section: Resultsmentioning
confidence: 99%
“…b, the rhombohedral symmetry is characterized by the splitting of (003)/(021) peaks at ∼40° in the 0.94(Bi 0.984 Er 0.016 Na) 0.5 TiO 3 –0.06BaTiO 3 ceramics sintered at 1080–1240 °C for 2 h; and the splitting of (002)/(200) peaks between 46° and 48° are simultaneously observed, corresponding to a tetragonal symmetry. To our knowledge, the simultaneous existence of (003)/(021) peaks at ∼40° and (002)/(200) peaks at ∼46.5° has been frequently considered as a main characteristic of the formation of rhombohedral and tetragonal MPB in BNT‐based materials . However, some researchers reported that the splitting of peaks can be suspected resulting from Kα1 (1.54056 Å) and Kα2 (1.54439 Å) radiations .…”
Section: Resultsmentioning
confidence: 99%
“…To improve the electric properties and to enhance the energystorage density of NBT -BT ceramics, the effects of A -Site, B -Site or simultaneous A and B sites substitution with rare earth (RE) elements were extensively studied. It has been reported that the partial substitution of some rare-earth ions such as Ho 3+ /Dy 3+ /Nd 3+ and Er 3+ for Bi 3+ in NBT based lead free ceramics can develop new multifunctional materials with excellent structural, dielectric, ferroelectric, piezoelectric, photoluminescent and other optical properties [19][20][21][22]. As the Gadolinium (Gd 3+ ), is a rare earth ion, wellknown for its improving character of pyroelectric properties [23].…”
Section: Introductionmentioning
confidence: 99%
“…[8] These issues were addressed by several research groups by approaching different methods with the help of specific site substitution and fabricating solid solutions (like rare earth-doped NBT-BT) with higher symmetry matrix to minimization of E c and conductivity which is useful for the storage device applications. [9,10] Over past few decades, sporadic progress was made on dielectric systems due to their relatively low response of electrocaloric effect (ECE) as compared to other candidates. [11,12] The indirect method gives the justification for finding the ECE from polarization curves over the functional temperature with the help of Maxwell relations .…”
Section: Introductionmentioning
confidence: 99%